How do language users feel the lack of beautiful words in public discussions? (on the example of the TV program „Szkło kontaktowe” and „Drugie śniadanie mistrzów”) - Kaczor, Monika (Papers in Linguistics, 2020)
The aim of the article is to discuss the aspects of linguistic aesthetics in public discourse, especially those that are desired by language users who are observe ongoing debates. Lack of sensitivity to the word, linguistic intuition and tact in language result in a decrease in the level of language culture in interpersonal relations. People who discuss the quality of language are disgusted by pauperization of language canons, violation of linguistic norms and the aesthetic order of thought, as well as brutality and vulgarity in speaking about those fragments of reality that are the subject of public disputes. While discussing the issue of skipping the beauty of language in public discussions, I refer to the method of axiolinguistic analysis. I refer to the principles of ethics of interpersonal communication, linguistic sensitivity and decency in language. I also present the influence of language aggression on the disappearance of linguistic aesthetics and the ethics in the public discourse. Public disputes revealed an important element of media culture. They showed that for the language users, the sense of aesthetics, the culture of the word and the beauty of the language are not without significance.